Wahhabi Islam facing the challenges of modernity : Dar al-Ifta in the modern Saudi state - Al-Atawneh, Muhammad K. (Studies in Islamic Law and Society, 2010)
This book focuses on the history and work of the Saudi Dār al-Iftā, one of the most central modern Islamic official religious institutions. The study was undertaken from two perspectives: (1) Dār al-Iftā creation, power structure, functions and the sociopolitical environment in which it operates; and (2) The actual work of this institution, mainly the mechanisms by which modern Saudi state muftis cope with clashes between Wahhābī idealism and the reality of an evolving society. This is a critical work which updates the readers' grasp of contemporary law and society in the modern Saudi state, in particular, and in Islamic jurisprudence in general.